Estratégia de ensino anatômico a violonistas para prevenção de lesões do aparelho locomotor - Somera Junior, Renato (2012)
Introduction: Acoustic Guitar players represent the most part of the instrumentalists and their activities involve repetitive efforts or static posture, which makes them likely candidates to develop labor disease, most times due to absolute lack of information. The objective of this study was to prepare an illustrative manual of the locomotor system, specifically directed to guitarists, for injury prevention. Method: 61 guitarists (students, professors, semi-professionals and professionals) in the city of São José do Rio Preto SP were taken into consideration, with the application of a questionnaire in order to estimate knowledge on bones, muscles and joints intrinsically associated with the praxis of guitar musical performances. As results, 83.5 % of the respondents had no specific anatomical knowledge, 62.3 % received no orientation on the best physical postures to perform the guitar; 63.93 % do not effect prior stretching for upper limbs or other body regions; 50.82 % do not practice muscle warming before the practice, and 52.46 % do not make pauses during the activity. Body areas that were constantly used during practice with the guitar encompassed right wrist (70.49%), left wrist (59.01%), right hand (63.93%) and left hand (50.81%). Spearman's correlation was used to estimate the relation between discomfort and hours of daily practice with guitar and it indicated positive correlation of low degree on right (r=0.3536) and left wrists (r=0.3226) and on the left hand (r=0.3431). Production of Illustrated Manual of Human Anatomy specific to the Locomotor System promotes teaching strategy to prevent injuries, traumas or musculoskeletal origin pathologies of guitarists, from complete beginners to instrumentalists.